The Effect of Guided Inquiry and Modified Free Inquiry on The Critical Thinking of VII Class Students of SMP Negeri 25 Pekanbaru - Nurhayati, Nurhayati; Wulandari, Sri; Suryawati, Evi (FKIP-Universitas Riau, 2021)
This study aims to determine the effect of guided inquiry models and modified free inquiry on critical thinking in the classification of living things. This research was conducted at SMPN 25 Pekanbaru. The research was carried out in the form of an experiment. The study population was class VII. The sample was taken using simple random sampling technique, which consisted of 3 classes, namely the experimental class 1 using the guided inquiry model, the experimental class 2 using the modified free inquiry model and the control class using the conventional method. The research design used a pretest and posttest control group design. Data were analyzed by using ANOVA test (one way ANOVA). Based on the result data, the average critical thinking result of the classification of living things with an average value of the experimental class 1 is 77.84 (good), the experimental class 2 is 70.93 (good) and the control class is 43.29 (poor). In the experimental class class 1, the critical thinking average is higher than the experimental class 2 and the control class. Based on the results of the ANOVA test, it was stated that the use of guided inquiry models and modified free inquiry had a significant effect on students' critical thinking in the experimental class 1, the experimental class 2 and the control class with a significant value (0.000) <alpha (0.05).